Passing Off yang Dilakukan Oleh Pihak yang Beritikad Tidak Baik Melalui Pemakaian Nama Perseroan Terbatas - Kimham Pentakosta; Elly Hernawati (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2020)
This paper focuses on the similarity of functions between Trademarks and Limited Liability Company Name, namely quality assurance function, which enables both to provide a guarantee on the reputation of goods and/or services offered to the consumer. Such similarity of functions between those two different legal terminology opens a loophole for any party, based on bad faith, to conduct passing off towards a registered trademarks owned by another party through the use of a limited liability company name. This paper shows the urgency of a harmonization and integration between the mechanism of applying for Trademark registration and the submission of the name of a limited liability company in Indonesia. Therefore, this paper will examine and criticize the laws and regulations relating to the two terminology above, inter alia the Law Number 20 of 2016 regarding Trademarks and Geographical Indications and the Government Regulation Number 43 of 2011 regarding Procedures for Filing and Use of Limited Liability Company Name. This paper concludes that the government of the Republic of Indonesia must immediately amend the regulation on the requirements for submitting the name of a limited liability company, by requiring the Directorate General of General Legal Administration to reject the name of a limited liability company that uses a name that has been registered as a brand by another party.